PROMOSI JABATAN PIMPINAN TINGGI PRATAMA (Studi Kasus Pada Badan Kepegawaian Daerah Kabupaten Merauke) - Welem Levi Betaubun; Sulaiman Asang; Hamsinah Hamsinah (SOCIETAS, 2018)
This study aims to: (1) describe and analyze the Promotion of Primary High Leadership Position in Merauke Regency, and (2) To describe and analyze the Promotion of Primary High Leadership Position in Merauke Regency. The researches used are qualitative. Data collection is used with observation, interview and documentation techniques. Data analysis used is a qualitative descriptive approach. The results showed that the Promotion Process of Primary High Position in Merauke Regency was in accordance with the mandated PERMENPAN Number 13 of 2014, but not in accordance with Government Regulation Number 11 of 2017 concerning Management of Civil Servants, related to the Requirements to be appointed in the Primary JPT. In the findings there are 5 positions whose leaders are over 56 years old and 1 D-II education person. Gender is one of the most dominant factors where most high-ranking officials are male. Then the age factor, most applicants who occupy positions aged over 51 years, because age provides an overview of the experience and length of work of someone to be able to occupy a position, and finally the factor of education where most of them are masters. Keywords: Promotion of Primary High Leadership Position, State Civil Apparatus